Ni-NiO heterojunctions: a versatile nanocatalyst for regioselective halogenation and oxidative esterification of aromatics - Bhardwaj N.; Singh A.K.; Tripathi N.; Goel B.; Indra A.; Jain S.K. (My University, 2025)
Herein, we report a facile method for the synthesis of Ni-NiO heterojunction nanoparticles, which we utilized for the nuclear halogenation reaction of phenol and substituted phenols usingN-bromosuccinimide (NBS). A remarkablepara-selectivity was achieved for the halogenated products under semi-aqueous conditions. Interestingly, blocking of thepara-position of phenol offeredortho-selective halogenation. In addition, the Ni-NiO nanoparticles catalyzed the oxidative esterification of carbonyl compounds with alcohol, diol or dithiol in the presence of a catalytic amount of NBS. It was observed that the aromatic carbonyls substituted with an electron-donating group favoured nuclear halogenation, whereas an electron-withdrawing group substitution in carbonyl compounds facilitated the oxidation reaction. In addition, the catalyst was magnetically separated and recycled 10 times. The tuned electronic structure at the Ni-NiO heterojunction controlled selectivity and activity as no suchpara-selectivity was observed with commercially available NiO or Ni nanoparticles. © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique 2021.